Simulation of The Backpropagation Method on Durability Value Using Starbit Asphalt Against Soaking Time - Saleh Alfian; Lubis Fadrizal; Rahim Afdhal (Universitas Islam Sultan Agung, 2024)
Starbit is a kind of celestial object elastomeric polymer asphalt that has been given additives. The advantages Starbit Asphalt are that it has high resistance to temperature and deformation and has good adhesion and cohesion. The purpose of this research is to calculate the durability value and try to use simulation. The research methodology encompasses simulating the backpropagation method and performing an experimental investigation in a tightly controlled laboratory setting. involves conducting an experimental investigation in a controlled laboratory setting. The durability testing encompasses different periods of time, such as thirty minutes, twelve hours, forty-eight hours, sixty-two hours, and ninety-six hours. The test results yielded an optimum asphalt content of 6.19%, which will be utilized for the production of durability samples. The test findings indicate that the durability value satisfies the criteria set by the 2018 Bina Marga Specification revision 2, which requires a minimum of 90% durability. Therefore, the material meets the durability requirements and can be utilized. After testing, the backpropagation method is simulated with stability values. The simulation results with the backpropagation method obtained the durability value with a maximum error value of 0.16% and the smallest value of -0.0068% error. So it can be concluded that the backpropagation method is considered capable of predicting durability values with an error of less than 50%. To obtain maximum results in further research, it is recommended to use.